Repetitive Fed-Batch: A Promising Process Mode for Biomanufacturing With E. coli - Kopp, Julian; Kittler, Stefan; Slouka, Christoph; Herwig, Christoph; Spadiut, Oliver; Wurm, David J. (Frontiers in Bioengineering and Biotechnology, 2020)
Recombinant protein production with E. coli is usually carried out in fed-batch mode in industry. As set-up and cleaning of equipment are time- and cost-intensive, it would be economically and environmentally favourable to reduce the number of these procedures. Switching from fed-batch to continuous biomanufacturing with microbials is not yet applied as these cultivations still suffer from time-dependent variations in productivity. Repetitive fed-batch process technology facilitates critical equipment usage, reduces the environmental fingerprint and potentially increases the overall space-time yield. Surprisingly, studies on repetitive fed-batch processes for recombinant protein production can be found for yeasts only. Knowledge on repetitive fed-batch cultivation technology for recombinant protein production in E. coli is not available until now. In this study, a mixed feed approach, enabling repetitive fed-batch technology for recombinant protein production in E. coli, was developed. Effects of the cultivation mode on the space-time yield for a single-cycle fed-batch, a two-cycle repetitive fed-batch-, a three-cycle repetitive fed batch and a chemostat cultivation were investigated. For that purpose, we used two different E. coli strains, expressing a model protein in the cytoplasm or in the periplasm, respectively. Our results demonstrate that a repetitive fed-batch for E. coli leads to a higher space-time yield compared to a single-cycle fed-batch and can potentially outperform continuous biomanufacturing. For the first time, we were able to show that repetitive fed-batch technology is highly suitable for recombinant protein production in E. coli using our mixed feeding approach, as it potentially (i) improves product throughput by using critical equipment to its full capacity and (ii) allows implementation of a more economic process by reducing cleaning and set-up times.